Outcomes of patients with metastatic neuroendocrine lung neoplasms: typical versus atypical carcinoids - Tanaka, Hugo; Corassa, Marcelo Petrocchi; Freitas, Helano; Barros, Milton; Riechelmann, Rachel (Brazilian Journal of Oncology, 2021)
Introduction: Well-differentiated neuroendocrine pulmonary tumours (NETp) are morphologically classified as typical carcinoid (TC) and atypical carcinoid (AC). There are limited data on systemic treatment for metastatic disease. Objective: Our study evaluated the median progression-free survival of patients with metastatic tumours, comparing TC and AC status for different treatments. Methods: Retrospective series of patients with metastatic NETp treated from 2002 to 2019 in a large cancer centre were analysed. Our primary endpoint was progression-free survival according to morphological classification (TC vs. AC). All patients received at least one treatment modality (e.g., somatostatin analogue [SSA], chemotherapy [ChP], and everolimus [Eve]). Variables were analysed using the chi-square test, median progression-free survival (mPFS) rates (months), with comparisons evaluated by the log-rank test. Results: Twenty-seven patients were included: 44% with TC and 56% with AC. TC patients were on average 58-years-old, 83.3% were female, and 33.3% received more than one treatment. AC patients were on average 61-years-old, 66.7% were female, and 20% received more than one treatment. All patients were treated more frequently with SSA (TC: 75% vs. AC: 80%, p=0.756). Cisplatin and etoposide were the most frequent ChP regimen (TC: 75% vs. AC: 30%, p=0.248). Patients with TC and AC treated with SSA had higher mPFS in months (TC mPFS SSA: 14.5, Eve: 2.50, ChP: 4.0, SSA + Eve: 4.50; AC mPFS SSA: 7.50, Eve: 4.50, ChP: 7.50, SSA + Eve: 7.00). Conclusion: Although the statistical analyses did not show a significant difference between treatment, numerically, more patients with TC or AC experienced tumor control with SSAs, where the mPFS pairs showed a possible tendency to differentiate themselves from the other regimes (Eve and ChP).
Keywords: Carcinoid tumor; Typical carcinoid; Atypical carcinoid; Everolimus; Somatostatin analogue; Chemotherapy; Adjuvant/ Neuroendocrine tumor.